2019
DOI: 10.1183/13993003.01193-2018
|View full text |Cite
|
Sign up to set email alerts
|

High COPD prevalence at high altitude: does household air pollution play a role?

Abstract: Studies comparing chronic obstructive pulmonary disease (COPD) prevalence across altitudes report conflicting results. However, household air pollution (HAP), a major COPD risk factor, was mostly not accounted for in previous analyses and never objectively measured. We aimed to compare the prevalence of COPD and its risk factors between low-resource highlands and lowlands, with a particular focus on objectively measured HAP.We conducted a population-based, observational study in a highland (∼2050 m above sea l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
52
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 41 publications
2
52
0
1
Order By: Relevance
“…4 A study by Brakema et al, in Kyrgyzstan, during 2015-2014 found that the prevalence of COPD was directly associated with moderate to high PM 2.5 concentrations. 29 Also, Phosri et al, found that there was a significant relation between exposure to NO 2 , CO, PM 10 and increased hospital admissions because of pneumonia, COPD, and asthma in Bankok, Thailand; while O 3 and SO 2 were associated with hospital admission for COPD and asthma as well. 30 A study by Gao et al performed in Beijing, China, showed that short-term exposure to PM 2.5 , PM 10 , NO 2 , SO 2 , and CO caused hospitalization due to COPD.…”
Section: Introductionmentioning
confidence: 99%
“…4 A study by Brakema et al, in Kyrgyzstan, during 2015-2014 found that the prevalence of COPD was directly associated with moderate to high PM 2.5 concentrations. 29 Also, Phosri et al, found that there was a significant relation between exposure to NO 2 , CO, PM 10 and increased hospital admissions because of pneumonia, COPD, and asthma in Bankok, Thailand; while O 3 and SO 2 were associated with hospital admission for COPD and asthma as well. 30 A study by Gao et al performed in Beijing, China, showed that short-term exposure to PM 2.5 , PM 10 , NO 2 , SO 2 , and CO caused hospitalization due to COPD.…”
Section: Introductionmentioning
confidence: 99%
“…The level of air pollution is often measured by the concentration of particles of less than 2.5 µm in the air (PM2.5). The average PM2.5 levels measured by BRAKEMA et al [9] in the highlands of Kyrgyzstan were 290 μg·m −3 , and the maximum levels reached 5822 μg·m −3 . This contrasts with the World Health Organization recommended 24-h level of 25 μg·m −3 .…”
mentioning
confidence: 76%
“…The study reported by BRAKEMA et al [9] is a welcome addition to the still limited literature on household air pollution and health in low and middle income settings [16]. Studies on the effects of long term exposure to air pollution are especially needed, as the current estimates of global burden of disease at high pollution levels are based on cohort studies in high income countries (with low levels) and extrapolations based on exposure to passive and active smoking [18].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3 Around 400 million people live in high altitude (>1500 meters above sea-level) and this geographical altitude is associated with COPD prevalence, and adaptation mechanism of these patients. 4 In COPD patients living in high altitude areas, altitude could induce a higher growth of airways relative to lung size, causing to an increased FEV1/FVC ratio and it may cause chronic hypoxia. 5 In high altitude, to compensate for the low pressure of oxygen, many physiological changes occur in the human blood circulation.…”
Section: Introductionmentioning
confidence: 99%